The role of the chemokine receptor XCR1 in breast cancer cells - Yang XL (Dove Medical Press, 2017)
Xiao Li Yang,1,* Li Guo Qi,2,* Feng Juan Lin,1 Zhou Luo Ou1 1Department of Oncology, Breast Cancer Institute, Fudan University, Shanghai Cancer Center, Shanghai, 2Department of Neurosurgery, Taian City Central Hospital, Taian, Shangdong, People’s Republic of China *These authors contributed equally to this work Abstract: Considerable attention has recently been paid to the application of chemokines to cancer immunotherapy due to their complex role in cell proliferation, invasion, metastasis, and tumorigenesis, which extends beyond the regulation of lymphocyte migration during immune responses. The expression and the function of the chemokine receptor XCR1 on breast cancer have remained elusive to date. In this study, the expressions of XCR1 mRNA were tested by quantitative real-time polymerase chain reaction in one breast epithelial cell line (MCF-10A) and nine breast cancer cell lines (MDA-MB-231, 231HM, 231BO, MDA-MB-468, MCF-7, T47D, Bcap-37, ZR-75-30, and SK-BR-3). We established XCR1-overexpressing breast cancer cell line MDA-MB-231 (231/XCR1) in XCR1 low expression cell line MDA-MB-231 (231). The ability of proliferation, invasion, and metastasis was measured by CCK8, plate cloning formation, and transwell analysis, respectively, in XCR1-overexpressing breast cancer cell lines (231/XCR1) and their parental cell line MDA-MB-231/Vector (simplified as “231/Vector”); 5×106/100 μL cells were inoculated in mammary fat pad of BALB/c nude mice. There were six BALB/c nude mice in the experimental group and control group. Protein expression was analyzed by cell immunofluorescence and Western blot. The growth of XCR1-overexpressing human breast cancer cell line MDA-MB-231 in vitro was restrained and tumorigenesis in vivo was also extenuated, its mechanism may involve in the inhibition of MAPK and PI3K/AKT/mTOR signaling pathway, but increase in LC3 expression. However, the overexpression of XCR1 in human breast cancer cell line MDA-MB-231 in vitro can promote the migration and invasion partially due to decreasing the protein level of β-catenin. Therefore, XCR1 can affect the biological characteristics of some special breast cancer cells through complex signal transduction pathway. Keywords: breast cancer, function, XCR1, proliferation